Fluorescent Detection of Vestibular Schwannoma Using Intravenous Sodium Fluorescein In Vivo. Issue 4 (April 2021) - Szczupak, Mikhaylo; Peña, Stefanie A.; Bracho, Olena; Mei, Christine; Bas, Esperanza; Fernandez-Valle, Cristina; Liu, Xue-Zhong; Telischi, Fred F.; Ivan, Michael; Dinh, Christine T.
Abstract : Background: Vestibular schwannoma (VS) are intracranial tumors caused by merlin deficiency. Sodium fluorescein (SF) is a fluorescent compound that accumulates in various intracranial tumors, causing tumors to emit green fluorescence after blue light excitation. Hypothesis: Intravenous SF preferentially deposits in VS, helping surgeons differentiate tumor from surrounding tissue. Methods: Merlin-deficient Schwann cells were grafted onto cochleovestibular nerves of immunodeficient rats. Rats were randomized to receive SF (7.5 mg/kg; n = 5) or saline (n = 3). Tissues were harvested at 1 hour and photographed in white and blue light. Sixteen surgeons identified and marked the tumor-tissue interfaces on images. Fluorescence was measured on tissue specimens using the IVIS imaging system and on tissue cross-sections obtained with confocal microscopy. Western blot was performed to measure levels of organic anion transporting polypeptide (OATP), a drug transporter specific for SF. Results: Under blue light, tumors from SF rats demonstrated bright green fluorescence under direct visualization, higher fluorescence measurements on tissue specimens ( p < 0.001), and more SF deposition on tissue cross-sections ( p < 0.001), when compared with surrounding tissues and placebo rats. Surgeons were better able to distinguish the tumor-tissue interfaces in SF rats. Furthermore, the expression level of OATP1C1 was significantly higher in tumors than in surrounding tissues ( p < 0.0001). Conclusion: In a xenograft model of VS, intravenous SF preferentially deposits in tumors, compared with normal surrounding tissue. Under blue light, tumors emit an intense green fluorescence that can help surgeons differentiate tumor from critical structures nearby, which may improve clinical outcomes in complicated VS surgery.